2020
DOI: 10.1021/acs.analchem.0c00111
|View full text |Cite
|
Sign up to set email alerts
|

Capability of CI-Orbitrap for Gas-Phase Analysis in Atmospheric Chemistry: A Comparison with the CI-APi-TOF Technique

Abstract: Chemical ionization Orbitrap mass spectrometry (CI-Orbitrap) represents a promising new technique for gas-phase analysis in analytical and atmospheric chemistries mainly due to its very high mass resolving power. In this work, we performed the first side-by-side comparison between a CI-Orbitrap and the widely used atmospheric pressure interface time-of-flight mass spectrometry (CI-APi-TOF) using two different chemical ionization methods, i.e., acetate-ion-based (CH 3 COO -) and aminium-ionbased (n-C 3 H 7 NH 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 49 publications
4
51
0
1
Order By: Relevance
“…In this study, we report the in-situ structural characterization of gas-phase HOMs, RO 2 radicals, and dimeric products of αpinene and limonene ozonolysis based on online MS/MS using an ultrahigh-resolution Orbitrap mass spectrometer equipped with a NO 3chemical ionization (CI) source 44,45 . Using online MS/MS data, aided by known structure-specific fragmentation patterns from existing offline MS/MS literature, we are able to infer the most plausible isomers of different compounds.…”
mentioning
confidence: 99%
“…In this study, we report the in-situ structural characterization of gas-phase HOMs, RO 2 radicals, and dimeric products of αpinene and limonene ozonolysis based on online MS/MS using an ultrahigh-resolution Orbitrap mass spectrometer equipped with a NO 3chemical ionization (CI) source 44,45 . Using online MS/MS data, aided by known structure-specific fragmentation patterns from existing offline MS/MS literature, we are able to infer the most plausible isomers of different compounds.…”
mentioning
confidence: 99%
“…However, it is important to mention that the Orbitrap provides non-linear responses when the concentrations of the analytes are very low (i.e., < 1 × 10 6 molecules cm -3 , at a 10-minute integration time). As a result, the calculated isotope abundance may deviate from its true value (Riva et al, 2020).…”
Section: Peak Identification Identifying the Abundances And Chemicalmentioning
confidence: 97%
“…Computational approaches, including ion deconvolution procedures, are required to partly resolve this limitation in order to extract the maximum possible information content (Cubison and Jimenez, 2015;Meija and Caruso, 2004;Zhang et al, 2019aZhang et al, , 2019b). To overcome these limitations, we have coupled a high-resolution mass spectrometer (Orbitrap, Eliuk and Makarov 2015) with a CI source (Riva et al, 2019a(Riva et al, , 2020 and an extractive ESI (EESI) inlet (Lee et al, 2020) for online analysis. Similarly, Zuth et al (2018) have combined an atmospheric pressure chemical ionization (APCI) interface to an Orbitrap and have shown that such a technology can achieve much greater mass resolving power at similar detection limit for the real-time measurement of organic aerosols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biogenic and anthropogenic sources emit a wide variety of volatile organic compounds (VOCs) into the atmosphere (Hallquist et al, 2009;Shrivastava et al, 2017). Once emitted, VOCs can quickly react with different atmospheric oxidants (OH radicals, O 3 , NO 3 radicals, or Cl atoms) yielding a wide variety of oxidized VOCs (OVOCs) spanning a broad range of chemical formulae and, thus, volatilities (Hallquist et al, 2009;Li et al, 2020;Wennberg et al, 2018).…”
Section: Introductionmentioning
confidence: 99%